Epigallocatechin gallate (EGCG) suppresses lipopolysaccharide‐induced inflammatory bone resorption, and protects against alveolar bone loss in mice. Issue 1 (12th June 2015) - Tominari, Tsukasa; Matsumoto, Chiho; Watanabe, Kenta; Hirata, Michiko; Grundler, Florian M.W.; Miyaura, Chisato; Inada, Masaki
Abstract : Epigallocatechin gallate (EGCG), a major polyphenol in green tea, possesses antioxidant properties and regulates various cell functions. Here, we examined the function of EGCG in inflammatory bone resorption. In calvarial organ cultures, lipopolysaccharide (LPS)‐induced bone resorption was clearly suppressed by EGCG. In osteoblasts, EGCG suppressed the LPS‐induced expression of COX‐2 and mPGES‐1 mRNAs, as well as prostaglandin E2 production, and also suppressed RANKL expression, which is essential for osteoclast differentiation. LPS‐induced bone resorption of mandibular alveolar bones was attenuated by EGCG in vitro, and the loss of mouse alveolar bone mass was inhibited by the catechin in vivo . Abstract : We examine the role of EGCG, a major polyphenol in green tea, in bone metabolism. LPS is a pathogen‐associated molecule, and induces inflammatory bone resorption. EGCG suppresses the LPS‐induced PGE production in osteoblasts. EGCG suppresses the LPS‐induced bone resorption of alveolar bones in vitro . In the mouse model of periodontitis, EGCG restores the loss of alveolar bone mass.